Neutronics feasibility of using Gd₂O₃ particles in VVER-1000 fuel assembly - Hoang , Van Khanh; Hoang Thanh , Phi Hung; Tran , Hoai Nam (Nuclear Science and Technology, 2016)
Neutronics feasibility of using Gd2O3 particles for controlling excess reactivity of VVER-1000 fuel assembly has been investigated. The motivation is that the use of Gd2O3 particles would increase the thermal conductivity of the UO2+Gd2O3 fuel pellet which is one of the desirable characteristics for designing future high burnup fuel. The calculation results show that the Gd2O3 particles with the diameter of 60 µm could control the reactivity similarly to that of homogeneous mixture with the same amount of Gd2O3. The power densities at the fuel pin with Gd2O3 particles increase by about 10-11%, leading to the decrease of the power peak and a slightly flatter power distribution. The power peak appears at the periphery pins at the beginning of burnup process which is decreased by 0.9 % when using Gd2O3 particles. Further work and improvement are being planned to optimize the high power peaking at the beginning of burnup.